Laparoscopic-assisted resection of lymphangioma that originated from the mesorectum—a case report - ITO, Norio; NAKAYAMA, Ataru; OGIWARA, Hiroaki; YOSHIZAWA, Junichi; TAKEUCHI, Nobumichi; KUBO, Naoki (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2012)
Intraperitoneal lymphangioma commonly shows slow growth without any typical symptoms. A 52-year-old woman, who had undergone probe laparotomy after being diagnosed with a right ovarian tumor in another hospital 7 years ago, was admitted for defecatory and urinary urgency. Computed tomography (CT) and magnetic resonance imaging showed a pelvic polycystic tumor compressing the rectum from the sacral side. CT also showed a branch of the superior rectal artery passing among the cystic components of the tumor. Laparoscopic-assisted tumor resection without colonic resection was perfomed after the patient was diagnosed with lymphangioma originating from tne mesorectum, and the patient was discharged 10 days after the surgery since she showed an uneventful recovery. Congenital lymphangioma is commonly detected in childhood, and acquired intraperitoneal lymphangioma is considered to be caused by pregnancy, trauma, and intraperitoneal inflammation. Since lymphangioma is benign and shows less invasive growth, laparoscopic surgery is a promissing option for its resection.